African American church-based HIV testing and linkage to care: assets, challenges and needs. Issue 6 (2nd June 2016) - Stewart, Jennifer M.; Thompson, Keitra; Rogers, Christopher
Abstract: The US National HIV AIDS strategy promotes the use of faith communities to lessen the burden of HIV in African American communities. One specific strategy presented is the use of these non-traditional venues for HIV testing and co-location of services. African American churches can be at the forefront of this endeavour through the provision of HIV testing and linkage to care. However, there are few interventions to promote the churches' involvement in both HIV testing and linkage to care. We conducted 4 focus groups ( n = 39 participants), 4 interviews and 116 surveys in a mixed-methods study to examine the feasibility of a church-based HIV testing and linkage to care intervention in Philadelphia, PA, USA. Our objectives were to examine: (1) available assets, (2) challenges and barriers and (3) needs associated with church-based HIV testing and linkage to care. Analyses revealed several factors of importance, including the role of the church as an access point for testing in low-income neighbourhoods, challenges in openly discussing the relationship between sexuality and HIV, and buy-in among church leadership. These findings can support intervention development and necessitate situating African American church-based HIV testing and linkage to care interventions within a multi-level framework.